Solvent-free MALI-MGRE Procedure for Synthesizing 1,4-thiazolidin-4- one MALI (Mercaptoacetic Acid Looking Imine) MGRE (Mechanical Grinding Reaction Equipment) - da Silva Santos, Jonas; Junior, Joel J.; da Silva, Flavia Martins (Current Organic Synthesis, 2023)
Background: 1,3-Thiazolidin-4-ones are heterocycles whose importance in the pharmaceutical market has already been established. Many of these synthetic derivatives, which contain a thiazolidinone nucleus, are currently used in various commercial formulations or are already in clinical trials for the treatment of disease for their anticonvulsant, antihypertensive and antidiabetic activities in addition to their activity against Streptomyces. 1,3-Thiazolidin-4-ones are produced mainly by cyclo condensation between an imine (generated in situ by the reaction of an aldehyde with an amine) and α-mercaptoacetic acid, known as the MALI (Mercaptoacetic Acid Looking Imine) reaction. Objective: A solvent-free methodology was developed to synthesize a 1,3-thiazolidin-4-one family by the MALI reaction. An apparatus was developed to grind a solid-liquid mixture of anilines, benzaldehydes and thioglycolic acid to activate the reaction. This apparatus was named MGRE (mechanical grinding reaction equipment). Methods: Substituted aniline 2 (4 mmol), substituted benzaldehyde 1 (4 mmol) and thioglycolic acid 3 (12 mmol) were placed in a mortar. The reagents were macerated using the MGRE at room temperature for a specified time period. At the end of the reaction, the product was poured into ice, the precipitate formed was neutralized (with 5% NaHCO3), and the solution was extracted in ethyl acetate and dried in MgSO4. The solid was recrystallized from MeOH/H2O. Results: The developed MGRE is a modification of a rod used in a mechanical stirrer. This adaptation is inexpensive and simple in construction, and it enables reactions to occur over long periods of time that would be exhaustive for manual grinding. Fifteen (1,3) thiazolidin-4-ones were produced. The products were synthesized using the solvent-free MALI-MGRE procedure. Conclusions: The MALI-MGRE methodology developed to produce 1,3-thiazolidin-4-ones showed a good reaction scope, has an easy work-up and is solvent-free. Consequently, MALI-MGRE is classified as a green methodology. An innovation of this study is the construction of the MGRE, which involves modifying the rod in a mechanical stirrer. The equipment is easy and inexpensive to construct and may be useful for various reactions involving grinding.
Keywords: MGRE